2009
DOI: 10.1108/00251740910929696
|View full text |Cite
|
Sign up to set email alerts
|

Corporate citizenship in football: delivering strategic benefits through stakeholder engagement

Abstract: PurposeThe purpose of this paper is to explain that corporate citizenship refers to the specific activities that an organisation engages in to meet social obligations, and which has become an issue of growing importance within the business community. A key area in academic literature concentrates on justifying corporate citizenship initiatives to the corporate sector by illustrating a range of strategic benefits that a firm can achieve. This study is located within this body of work and aims to illustrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 28 publications
1
77
0
5
Order By: Relevance
“…The authors present a conceptual model that describes the creation of value for external stakeholders: financial value (e.g., for television channels, sponsors and sporting goods manufacturers), cultural value (e.g., for local communities), human value (e.g., for non-governmental organizations) and reassurance value (e.g., for economic and political actors and the population). From the study of Charlton Athletic and Brentford football clubs which have established a charitable structure involved in socially responsible activities in the areas of health, education, social inclusion and community integration, Walters and Chadwick (2009) emphasize the strategic advantages (the removal of commercial and community tensions, reputation management, brand building, local authority partnerships, commercial partnerships, and player identification) that a football club can draw from the implementation of citizenship-orientated activities through a stakeholder engagement model based on the creation of a community trust model of governance. Walters and Tacon (2010) also focus their attention on how the concept of social responsibility can be implemented by sports organizations through stakeholder management strategies in the UK football industry.…”
Section: Applications Of the Stakeholder Approach To Professional Foomentioning
confidence: 99%
See 2 more Smart Citations
“…The authors present a conceptual model that describes the creation of value for external stakeholders: financial value (e.g., for television channels, sponsors and sporting goods manufacturers), cultural value (e.g., for local communities), human value (e.g., for non-governmental organizations) and reassurance value (e.g., for economic and political actors and the population). From the study of Charlton Athletic and Brentford football clubs which have established a charitable structure involved in socially responsible activities in the areas of health, education, social inclusion and community integration, Walters and Chadwick (2009) emphasize the strategic advantages (the removal of commercial and community tensions, reputation management, brand building, local authority partnerships, commercial partnerships, and player identification) that a football club can draw from the implementation of citizenship-orientated activities through a stakeholder engagement model based on the creation of a community trust model of governance. Walters and Tacon (2010) also focus their attention on how the concept of social responsibility can be implemented by sports organizations through stakeholder management strategies in the UK football industry.…”
Section: Applications Of the Stakeholder Approach To Professional Foomentioning
confidence: 99%
“…Most of these studi es were focused on British clubs (Michie and Oughton, 2005;Walters and Chadwick, 2009;Walters and Tacon, 2010;Walters, 2011;Healy and McDonagh, 2013;Morrow, 2013). The other ones were based on French (Senaux, 2004(Senaux, , 2008 and Turkish (Sarikaya et al, 2012) clubs or on a broader sample of European (Paché and N'Goala, 2011) or World (Breitbarth and Harris, 2008) clubs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 By the mid-1990s, football's potential had been elevated to be a position as a 'key' deliverer of policy objective for a range of social welfare issues, notable health.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this apparent mass media youth appeal (Smith & Westerbeek, 2007), it has received support as a vehicle to deliver on the social inclusion agenda. Within England, Football in the Community (FitC) programmes, which are often organised as independent registered charities attached to professional football clubs, lead the social welfare and corporate social responsibility agenda for football (Anagnostopoulos & Shilbury, 2013;Parnell et al, 2013;Walters, 2009;Walters & Chadwick, 2009). Watson (2000) originally suggested that FitC schemes are identified as organisations that can aid the development of a range of social outcomes including sport participation rates, drug and alcohol abuse, social exclusion and health (which has been echoed more recently by Parnell and Richardson, 2014).…”
Section: Introductionmentioning
confidence: 99%